Collaborative Project Based Learning using Office 365 during Covid-19 Outbreak - Wicaksono, Soetam Rizky; Suprapto, Edy (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study investigates the challenges students face in adapting to new teaching methodologies in remote learning environments and explores the efficacy of Project based learning (PBL) in such contexts. It also assesses the potential of Office 365, specifically Microsoft Teams, in facilitating collaborative learning. Our findings indicate that students face several challenges, including abrupt transition to online learning, inadequate preparation, and communication difficulties. However, when necessary adaptations and support were provided, PBL could be successfully implemented. The integration of Office 365 and Microsoft Teams significantly enhanced the collaborative learning process, offering robust tools for real-time interaction, shared document creation, and group work monitoring. This study highlights the potential of Office 365 and Microsoft Teams in creating effective remote learning experiences across diverse disciplines, suggesting they can be instrumental in overcoming distance learning challenges.